Open. : Inhoud: 50 x highlights uit de collectie. - Ex, Sjarel; Centraal Museum, Utrecht (Utrecht : Centraal Museum, 1999)
van Os, Pieter Gerardus ; Suuroonen, Matti ; Brugghen, Hendrick Jansz ter ; Atelier van Lieshout ; Rietveld, Gerrit ; Peeters, Sef ; Watanabe, Junya ; van Diemen, Marieke ; van Ravesteyn, Sybold ; Toorop, Charley ; Willink, Carel ; Koch, Pyke ; Hutten, Richard ; de Koning, Krijn ; van Bronchorst, Johannes Jansz ; van Scorel, Jan ; Droochsloot, Joost Cornelisz ; Schräder, Truus Schröder ; Neuman, Johan Heinrich ; van Nude, Jan ; Viktor & Rolf ; van Gogh, Vincent ; Lion Cachet, Carel Adolph ; Seyferth, Christoph ; Polhuis, Gerard ; Rist, Pipilotti ; van Doesburg, Theo ; Wtewael, Joachim ; Saverij, Roelant ; Courbet, Gustave ; Honthorst, Gerard ; Saenredam, Pieter Jansz ; Moreelse, Paulus Jansz ; van Honthorst, Gerard ; Verheyen, Jan Hendrik ; Moesman, Johannes Hendrikus ; van Scorel, Jan ; Bloemaert, Abraham ; van Borckeloo, Adam van VianenT.
biografie
publieksgids
Nederlands & Engels
boek